PENYELESAIAN SENGKETA AKAD MUDHARABAH MELALUI PENGADILAN AGAMA YOGYAKARTA (STUDI KASUS PUTUSAN NOMOR 193/Pdt.G/2021/PA.YK) - Habibullah (Mu'amalat: Jurnal Kajian Hukum Ekonomi Syariah, 2023)
Dispute resolution in the context of mudharabah contracts is important in the sharia financial system. The Yogyakarta Religious Court has a central role in resolving this kind of dispute in accordance with the principles of Islamic law. This study aims to analyze the decision of the Yogyakarta Religious Court with case number 193/Pdt.G/2021/PA.YK. related to resolving mudharabah contract disputes. In this decision, the Yogyakarta Religious Court based its decision on the principles of Islamic law, including the principles of justice, fulfillment of the rights of the parties, and relevant sharia considerations. The Yogyakarta Religious Court also considers the validity of the contract, the agreement between the parties, and the evidence presented at the trial.